Our experiences with laparoscopic transperitoneal adrenalectomy - Girgin, Mustafa; Çay, Ferhat (My University, 2018)
Introduction: The aim of this study was to evaluate the outcomes of laparoscopic transperitoneal adrenalectomy cases from our clinic.Materials and Methods: Laparoscopic transperitoneal adrenalectomy was performed on 51 patients between January 2010 and September 2017.Results: The mean age of the 51 patients was 53.81±14.006 years (range: 31–76 years). Of the total, 18(35%) were male and 33 (65%) were female. A right adrenalectomy was performed in 30 cases (59%) and aleft adrenalectomy in 21 cases (41%). All of the patients were operated on with a laparoscopic transperitoneal approach. Four patients experienced peroperative hemorrhage; however, hemostasis was achieved.There was no conversion to an open procedure in any of the patients. No hemorrhage requiring transfusion or other major complications developed postoperatively. The mean duration of the operation was102.8±21.6 minutes (range: 50–170 minutes). The mean tumor size was 3.8±2.6 cm (range: 2–12 cm)based on pathology specimens. The mean duration of hospital stay was 2.61±0.8 days (range: 2–6 days).The pathology results of the cases revealed surrenal adenomas in 17 cases, adrenal cortical adenomas in13 cases, pheochromocytoma in 8 cases, adrenal cortical neoplasms in 4 cases, adrenal pseudocysts in4 cases, adrenal nodular hyperplasia in 3 cases, malignant oncocytoma in 1 case, and an adrenal corticalneoplasm containing metastasis foci in 1 case.Conclusion: We believe that transperitoneal laparoscopic adrenalectomy is a safe and effective method forthe treatment of adrenal masses if the adequate technical equipment, experience, and knowledge are present
Keywords: Cerrahi